OSTEOPROTEGERIN AND BONE DENSITY - Stejskal, David; Zurek, Martin; Bartek, Josef; Jedelsky, Libor; Ruzicka, Viktor (Biomedical papers, 2001)
Aim of study was determine if a correlation exists between bone mass density and concentration of osteoprotegerin.We examined the group of 199 patients of mean age of 63 years. Of the group under study, 31 patients hadnormal bone density (T score >-1 and
Keywords: Osteoprotegerin / Bone density / Osteoporosis